Determination of Barreling of Aluminum Solid Cylinders During Cold Upsetting Using Genetic Algorithm - Kanca,Erdogan (2019)
ABSTRACT This study presents Genetic Programming models for the formulation of barreling of aluminum solid cylinders during cold upsetting based on experimental results. The maximum and minimum radii of the barreled cylinders having different aspect ratio (d/h= 0.5, 1.0 and 2.0) were measured for various frictional conditions (m=0.1-0.4). The change in radii with respect to height reduction showed different trends before and after folding, therefore, the corresponding reduction ratios of folding were also determined by using incremental upsetting. Genetic programming models were prepared using the experimental results with the input variables of the aspect ratio, the friction coefficient, and the reduction in height. The minimum and maximum barreling radii were formulated as output taking the folding into consideration. The performance of proposed GP models are quite satisfactory (R2 = 0.908-0.998).